Optimizing in the ECF bleaching conditions for producing final non-wood dissolving-like pulps with suitable viscosity levels - Pornthip Tongpisitsombat; Nazhad, Mousa M.; Bohez, Erik L.J.; Soni, Peeyush; Basta, Jiri; Royal Thai Government; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2013)
Industrial bagasse pulp mill after Kraft cooking, scree ning and washing was used in this study. The untreated pulp was treated in a standard Strong Alkali Treatment SAT under the following conditions : pulp consistency 12%, temperature 70oC, retention time 60 minutes, Peroxide charge 150 kg/tp. And then the pulp was D EP D bleached to a brightness above 85% ISO. The conditions in the EP stage were widely varied to obtain pulps with different viscosity levels. The SAT and the bleached pulps were evaluated in terms of important process and quality parameters (pH and residuals in the effluents and kappa number, brightness and viscosity of the D 0 , EP and D 1 pulps). On selected pulps, pentosan and alpha - cellulose content were measured since these parameters are important when optimizing the process of production of bleached dissolving - like bagasse pulps. It has been proven that a change in EP stage conditions during D EP D bleachi ng of SAT pretreated bagasse pulps may adjust the final pulp viscosity within rather broad viscosity range. There are several set ups in the EP stage which deliver a viscosity level of 550 - 600 SCAN units required for production of viscose pulp. When taking into consideration different process - technical parameters and final pulp quality, the alternatives using 10 - 15 kg peroxide / tp in the EP stage should be preferred. Strong alkali treatment conditions determine the pentosan and alpha cellulose contents but not so much the final pulp viscosity. On the other hand the conditions in EP stage of D EP D bleaching influence greatly the viscosity of the final D 1 pulps but have very limited effect on pulp{u2019} s pentosan and alpha cellulose content. Therefore, when optim izing the bagasse dissolving pulp quality, the pentosan and alpha cellulose levels in pulps should be set in the SAT treatment and the final viscosity should be fine - tuned by changing the conditions in the EP stage of D EP D bleaching. The standard SAT tr eatment as recommended in the literature for hardwood pulp was used in this study. However it was too soft for the bagasse pulps and therefore the targeted levels of pentosans and al pha - cellulose contents in the final bleached bagasse pulps could not be ac hieved. It is recommended to optimize the SAT treatment especially for the Bagasse pulps in order to achieve required levels of pentosans and alpha - cellulose in the final bleached bagasse pulps. Moreover, o xidized white liquor should be used as an alkali source, thus evaluating the possibilities for recovering the SAT effluents in the existing recovery system. Furthermore, other dissolving pulp parameters like R 18, clogging test (K w ) and the Fock ś number should be also determined thus supporting the optimization of the dissolving pulp production process
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Pulp and Paper Technology
Thesis (M. Sc.) - Asian Institute of Technology, 2013
Keywords: Papermaking; Bagasse; Wood-pulp -- Bleaching